2014
DOI: 10.1016/j.jbef.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Technical market indicators: An overview

Abstract: a b s t r a c tCurrent evidence on the predictability of technical analysis largely concentrates on pricebased technical indicators such as moving averages rules and trading range breakout rules. In contrast, the predictability of widely used technical market indicators such as advance/decline lines, volatility indices, and short-term trading indices has drawn limited attention. Although some market indicators have also become popular sentiment proxies in the behavioral finance field to predict returns, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 114 publications
(135 reference statements)
0
9
0
Order By: Relevance
“…This is far inferior to financial information. Fang et al (2014) studied the profitability of 93 market indicators and found no evidence that they could predict the stock market returns. Naz ario et al (2017) classified and coded the technical analysis documents of the past 55 years, focusing on the stock analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This is far inferior to financial information. Fang et al (2014) studied the profitability of 93 market indicators and found no evidence that they could predict the stock market returns. Naz ario et al (2017) classified and coded the technical analysis documents of the past 55 years, focusing on the stock analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that the research results 'supporting technical analysis' and 'not supporting technical analysis' account for almost equal proportions. A more detailed overview of the technical analysis can be found in Bustos and Pomares-Quimbaya (2020), Fang et al (2014), Gandhmal andKumar (2019), andNaz ario et al (2017). This is where the role and influence of the stock markets' TIs are systematically reviewed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The second family is the Trading Range Break (TRB) or support and resistance rule which generates a buy (sell) signal when the price rises above (falls below) the resistance (support) level, which refers to the highest (lowest) over the k most recent days. That technique has also widely been used in the previous empirical evidence with different results; see Bessembinder and Chan (1995), Hudson et al (1996), Shynkevich (2012), Yu et al (2013) and Fang et al (2014) among others.…”
Section: Technical Trading Rulesmentioning
confidence: 99%
“…It is being used now heavily by fund managers in most countries including the United states and is an important investment decision-making tool for short term traders. Technical Analysis has been defined in the literature as a science in terms of recording historical price changes in graphical form, and has been defined also as an art in terms of its great talent in discovering and identifying trend in an early stage letting traders and investors join the trend at the beginning and hold until an evidence for reversing the current trend (Pring 2002, P.3;Edward;Magee & Bassetti 2006, P.4;Fang;Qin and Jacobsen 2014;Shynkevich 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was believed that chart reading is of no real value to the stock market investors and traders (Bessembinder and Chan, 1995). Fang et al (2014); Fama and Blume (1966) and Jensen and Bennington (1970);Fama (1965Fama ( , 1970 However, a growing body of literature has been recognized recently that technical analysis could generate abnormal returns. For example (Zapranis & Tsinaslanidis 2012;Cervello-Royo;Guijarro & Michniuk 2015) for classical price patterns, (Marshall & Cahan 2005;Gustafsson 2012;Ülkü & Prodan 2013;Boboc & Dinică 2013;Baetje & Menkhoff 2016;Chen;Su & Lin 2016;El-Ansary & Atuea 2017) for technical indicators and (Brock;Lakonishok & LeBaron 1992;Bessembinder & Chan 1995) for both technical patterns and indicators.…”
Section: The Predicting Ability Of Technical Analysismentioning
confidence: 99%